Telaah Maqasid Syariah Terhadap Pelaksanaan Bantuan Langsung Tunai Dana Desa - Khoirul Anam; Riyanta Riyanta (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2022)
The state has issued a policy of Village Fund Direct Cash Assistance. The goal is to help village communities affected by the COVID-19 pandemic so they don't experience food insecurity. Despite the good intentions, the BLT-DD is still controversial, because it cannot target all the poor and affected by the existing COVID-19 pandemic. Lebak Village is one of the villages in the Grobogan sub-district where the poverty rate is relatively high, so it is impossible for BLT-DD to target all poor people in this village. This research includes field research using qualitative methods with juridical and maqashid shari'ah approaches and descriptive analysis. From the study conducted, it was found that: first, the implementation of BLT-DD in Lebak Village is still not in accordance with regulations, both Ministerial Decrees, Technical Guidelines and Circulars. Second, BLT-DD in Lebak Village has drawn a polemic because many did not involve the Covid task force and RT-RW when determining KPM. Third, the implementation of BLT-DD in Lebak Village in general has not reflected the values ​​of justice, benefits and legal policies because not all KPMs are poor, some are even rich and have cars.